Diﬀusion-Less Recrystallization at High Uniaxial Deformation - L.S. Metlov; A.V. Zavdoveev (Журнал нано- та електронної фізики)
It was shown by computer simulation that coarsened grains with lower content of defects are formed at uniaxial deformation of a four-grain inﬁnite nano-wire. The structure similar to crystal ﬁlaments was formed in the case of tension. The case of compression demonstrated formation of two grains (from four initial ones) disoriented at an angle of four degrees.